Peran Pusat Pembelajaran Keluarga dalam Kontrol Parenting Era Digital di Kelurahan Bendul Merisi Kota Surabaya - Prayitno, Mohammad Rexy; Priambodo, Bayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Family Learning Center plays a big role in developing parental control over the family, to prevent negative impacts that can damage the moral values of the nation's future generations. Through government-run programs, the Family Learning Center provides an understanding to citizens about the importance of monitoring their families. This research focuses on the application of Social Change theory and Rogers & Kincaid Communication. Data analysis is carried out using the interactive Miles and Huberman model in stages and interactively with the predetermined data. The Family Learning Center plays a very important role in improving family welfare. By using direct communication methods at the community hall, this program has successfully achieved its set targets.